Factors Influencing the Utilization of Inpatient Units: Demand, Provision and Policies Comprehensively in Literature Review - Sukawati, Sadewa Yudha; Ilyas, Jaslis (Syntax Corporation Indonesia, 2025)
The 2023 expansion of Indonesia's National Health Insurance (JKN) to 95.2% coverage and the rising burden of non-communicable diseases have driven increases in patient length of stay and inpatient visits, yet hospital bed distribution remains uneven across provinces, causing patient backlogs and delays in critical care. To comprehensively review demand, supply, and policy factors affecting inpatient unit utilization, measured by the Bed Occupancy Rate (BOR), in literature published from 2020 to 2025. A Literature Review was conducted using the PEOS framework (Patient, Exposure, Outcome, Studies). Articles were sourced from Science Direct, SpringerLink, and ProQuest, followed by deduplication, title/abstract screening, and full-text selection based on inclusion-exclusion criteria. The PRISMA flowchart guided the screening process to ensure alignment with PEOS. Out of 57 identified articles, 20 met the criteria for full analysis. Findings indicate that patient demand, bed supply capacity, and financing and referral policies significantly influence BOR. However, no study was found that integrates all three aspects comprehensively. Demand, supply, and policy are key determinants of hospital bed utilization. Further research examining their interactions is needed to develop strategic recommendations for capacity management and equitable access to inpatient services.